2021
DOI: 10.3390/jcm10132786
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Mental Health among COPD Patients in a Population-Based Sample in Spain

Abstract: (1) Background: To assess the prevalence of mental disorders (depression and anxiety), psychological distress, and psychiatric medications consumption among persons suffering from COPD; to compare this prevalence with non-COPD controls and to identify which variables are associated with worse mental health. (2) Methods: This is an epidemiological case-control study. The data were obtained from the Spanish National Health Survey 2017. Subjects were classified as COPD if they reported suffering from COPD and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…When the effect of smoking habit on mental health levels was examined, unlike our result, in the study of Fuentes-Alonso et al (2021), active smoking was associated with high mental distress. However, the low mental health level of all individuals in our study may not have made a difference in smoking habits.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…When the effect of smoking habit on mental health levels was examined, unlike our result, in the study of Fuentes-Alonso et al (2021), active smoking was associated with high mental distress. However, the low mental health level of all individuals in our study may not have made a difference in smoking habits.…”
Section: Discussioncontrasting
confidence: 87%
“…The difference may be due to the fact that the studies were conducted in different societies and the majority of our sample group consisted of male individuals. When other socio‐demographic factors were analysed, it was shown that living alone, low education and income level were associated with negative mental health in individuals with COPD in line with the literature (Fuentes‐Alonso et al, 2021; Mewes et al, 2016). When the employment status of the patients was examined, it was found that the patients who did not work had better mental health.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Even so, it is still more than three times higher in women than in men. Previous studies have demonstrated that depression, as well as other psychological disorders including anxiety and irritability, are more prevalent in women [ 17 , 18 , 19 , 20 ]. There are several sex-specific factors that could explain these results.…”
Section: Discussionmentioning
confidence: 99%
“…According to the biopsychosocial model, depression and anxiety may affect disease severity via mechanisms associated with poor treatment adherence and self-care. In addition, several factors such as smoking behaviour [ 68 70 ], physical activity levels [ 71 , 72 ], brain processes [ 62 , 73 , 74 ], sleeping patterns [ 75 , 76 ], inflammatory processes [ 15 , 77 ] and activation of cell-mediated immunity [ 78 ], fatigue [ 79 ] and genetic risk factors [ 80 , 81 ], are most likely involved as contributors or moderators, requiring future systematic studies. Moreover, biological stress systems in the brain ( e.g.…”
Section: Prevalence and Impact Of Psychological Distress In Copdmentioning
confidence: 99%